Experimental investigation of concrete strength curve based on pull-out post-insert method - Yuanxun Zheng; Weixing Kong; Mengen Ji; Chao Wan; Ehsan Moshtagh (International Journal of Distributed Sensor Networks)
As concrete is a building material that is widely used in the field of infrastructure construction, and its quality is related to the quality and service life in infrastructure engineering, concrete strength is an important reference index that reflects the concrete quality. Based on this, two commercial concretes A and B are selected in Henan Province, China, to perform the concrete strength test under same condition curing and standard condition curing in the pull-out post-insert method, cubic compression, rebound method, and drilling core method. The relationships between the different curing conditions, cubic compressive strength, core sample strength, rebound strength, and pull-out force of different commercial concretes are compared and analyzed. Through a comparative analysis and while considering the convenience and accuracy requirements, the strength curves of the two different concretes based on the pull-out post-insert method were fitted and analyzed, and the local strength curve test in Henan based on the pull-out post-insert method was established. The research results provide technical support for evaluating the strength of concrete structures using the pull-out post-insert method, which has important engineering significance for improving the popularize and application of the pull-out post-insert method.